Determinan Kejadian Campak Pada Anak Usia Balita di Kota Bukittinggi - Harisnal, Harisnal; Ediana, Dina (Jurnal Endurance, 2019)
The incidence of measles in the city of Bukittinggi has increased in 2016, namely 77 cases, 40 cases (51.9%) among them in infants. The initial survey of 10 samples found that 40% experienced measles, 50% never had measles immunization, 70% said they did not give exclusive breastfeeding when they were babies. The aim of the study was to determine the factors associated with measles in children under five. Analytical research method with case control design. The population of all children under five, suffering from measles in 2016 was 40 people. Samples were taken by total sampling, and control samples were taken matching. Data was collected through guided interviews and observations, and data was processed computerically with chi-square statistical tests. The results of univariate analysis revealed that 66.7% of the samples were in the control group (66.7%), measles immunization, 73.3%, exclusive breastfeeding, and 57.5% had densely populated homes. Bivariate results, there was a relationship between immunization status ( p = 0,000 and OR = 10.7), exclusive breastfeeding (p = 0.034 and OR = 2.667) and occupancy density (p = 0.003 and OR = 3.807). It was concluded that the factors associated with the incidence of measles were immunization status, exclusive breastfeeding and occupancy density. There needs to be counseling about the disease, continuity from the officers so that the community understands and is aware of the importance of efforts to prevent measles. Kejadian penyakit campak di Kota Bukittinggi mengalami peningkatan pada tahun 2016, yaitu 77 kasus, 40 kasus (51,9 %) diantaranya pada balita. Survei awal terhadap 10 sampel, didapatkan bahwa 40% mengalami kejadian campak, 50% tidak pernah melakukan imunisasi campak, 70% mengatakan tidak memberikan ASI eksklusif saat bayi, Tujuan penelitian untuk mengetahui faktor-faktor yang berhubungan dengan kejadian campak pada anak usia balita. Metode penelitian analitik dengan desain case control. Populasi seluruh anak usia balita, menderita penyakit campak pada tahun 2016 sebanyak 40 orang. Sampel diambil secara total sampling, dan sampel kontrol diambil secara matching. Data dikumpulkan melalui wawancara terpimpin dan observasi, dan data diolah secara komputerisasi dengan uji statistik chi-square. Hasil analisis univariat diketahui 66,7 % sampel merupakan kelompok kontrol, (66,7 %),  imunisasi  campak, 73,3 %, ASI eksklusif , dan 57,5 % memiliki rumah padat penghuni.Hasil bivariat, adanya hubungan antara status imunisasi (p=0,000dan OR =10,7), pemberian ASI eksklusif (p=0,034dan OR =2,667) dan kepadatan hunian (p=0,003dan OR =3,807). Disimpulkan faktor yang berhubungan dengan kejadian campak adalah status imunisasi, pemberian ASI eksklusif dan kepadatan hunian.Perlu adanya penyuluhan tentang penyakit, berkesinambungan dari petugas sehingga masyarakat lebih memahami serta menyadari tentang pentingnya upaya pencegahan penyakit campak.